Analysis of farmers’ perceptions of bench terracing innovation in the eastern and southern Ethiopian highlands - Alemayehu Temesgen Gebremikael; Jemal Yousuf Hassan; Getachew Shambel Endris; Chanyalew Seyoum Aweke (Sustainable Environment, 2024)
Land degradation threatens environmental and agricultural development in the 21st century. To alleviate this problem, bench terracing has been implemented in eastern and southern Ethiopia. This paper investigates how farmers perceive the attributes and effectiveness of bench terracing in Ethiopia. A Multi-stage sampling techniques were applied to select 384 sample households. For this study, data were collected through primary and secondary sources, and the collected data were analyzed using descriptive statistics and content analysis methods. Primary data were collected using semi-structured questionnaires, focus groups, and key informant interviews; secondary data came from local authority reports. We found that bench terraces restored damaged land and improved crop yield where they were aptly implemented and maintained. The findings also disclose that 57.3% of farmers perceived that bench terracing was more cost-effective; 60.7% responded that it is compatible with the socio-cultural context; and 59.8% perceived Its outcomes are observable to others. However, when a farmer lacks sufficient social, human, or financial capital holdings and capabilities, it often fails. We conclude that the technology was adopted through a multifaceted process, promoted or hindered by both its attributes and effectiveness. Policy-makers and Planners should center those restraints on designing, implementing, and maintaining bench terracing.